HUBUNGAN INTERTEKSTUAL PUISI “MUNIR MENENGGAK RACUN” KARYA YOSEPH YAPI TAUM DAN PUISI “SAJAK UNTUK SEBUAH NAMA (CAK MUNIR)” KARYA PRAMASTA SAID - Angela Klaudia Danu; Petrus Sii; Priska Filomena Iku; Claudia Oktafiani Samador (Unika Santu Paulus Ruteng, 2022)
This study aims to understand the depth of meaning of poetry which has an intertextual relationship with other poetry works. The researcher used Abrams's structural approach to analyze the similarities and differences between the poems that were analyzed. The method used in this study is a qualitative descriptive method. Sources of data in this study are the poem